Novel acaricide toxicities on Tetranychus urticae infesting Piper betle - REDDY, D SRINIVASA; LATHA, M PUSHPA (The Indian Journal of Agricultural Sciences, 2016)
Laboratory and field experiments were conducted to test novel acaricide efficacies for the management of two- spotted spider mite, Tetranychus urticae (Koch) on betelvine (Piper betle L.). The treatments were abamectin 1.9EC @ 0.3ml, 0.5ml and 0.7ml/l, propargite 57EC @ 2.5 and 3.0ml/l, fenazaquin 10EC @ 1.7ml/l, fenpyroximate 5EC @ 1.25ml/l, spiromesifen 22.9SC @ 0.8ml/l, and compared with conventional compounds, sulphur 80WDG @ 3g/l and dicofol 18.5EC @ 2.5ml/l. In laboratory studies, all the acaricides resulted in 14.47 to 85.53% mortality with highest in abamectin @ 0.7ml/l during I season and lowest in dicofol, whereas in II season lowest per cent mortality of 21.80 was recorded in sulphur and highest mortality of mites (83.40%) was noted in abamectin @ 0.7ml/l at 72h after treatment. The acaricides caused mortality of mites in the range of 16.27 of 90.98% during 10 day observation period in the field studies with highest in abamectin (0.7ml/l) treated plots followed by fenazaquin (59.44% at 10th day) and least mortality was showed by dicofol, i.e. less than 20% in first season but spiromesifen, fenpyroximate and propargite @ 3.0ml/l showed good efficacy, i.e. 51.40%, 46.37% and 40.37% mites mortality, respectively, at 10th day during I season trial. In II season, lower mortality of mites was recorded in dicofol (34.41%–16.99%) and sulphur (38.03% – 19.57%) on 1st and 10th day, respectively indicating that these acaricides lost their efficacy over a period of time but abamectin @ 0.7ml/l (90.35–70.39%) and 0.5ml/l (85.65–65.71%) throughout the observation period showed higher efficacy followed by fenazaquin (72.24–56.86%), spiromesifen (69.13–48.60), propargite @ 3ml/l (60.80–39.76%) and fenpyroximate (48.84–28.43%) at 1 and 10th day after spray observations. Abamectin and fenazaquin were superior over other acaricides tested under both conditions followed by spiromesifen, fenpyroximate and propargite.